2022
DOI: 10.1186/s41235-022-00376-8
|View full text |Cite
|
Sign up to set email alerts
|

Communication with face masks during the COVID-19 pandemic for adults with hearing loss

Abstract: Face masks have become common protective measures in community and workplace environments to help reduce the spread of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. Face masks can make it difficult to hear and understand speech, particularly for people with hearing loss. An aim of our cross-sectional survey was to investigate the extent that face masks as a health and safety protective measure against SARS-CoV-2 have affected understanding speech in the day-to-day lives of adults with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 25 publications
3
18
0
4
Order By: Relevance
“…This is especially important when one considers the impact that face masks have had on those with hearing loss. In a recent study, over 80% of adults who were deaf or hard of hearing reported difficulty understanding others who wore face masks ( Poon and Jenstad, 2022 ). Therefore, it should be noted that these types of studies focusing on visual posed stimuli do so while negating the vocal modality.…”
Section: Discussionmentioning
confidence: 99%
“…This is especially important when one considers the impact that face masks have had on those with hearing loss. In a recent study, over 80% of adults who were deaf or hard of hearing reported difficulty understanding others who wore face masks ( Poon and Jenstad, 2022 ). Therefore, it should be noted that these types of studies focusing on visual posed stimuli do so while negating the vocal modality.…”
Section: Discussionmentioning
confidence: 99%
“… 2021 ). Hearing loss is another factor that can affect perception of masked speech, and listeners with hearing loss report greater difficulties perceiving masked speech in a variety of situations (Poon and Jenstad 2022 ; Saunders et al. 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Hearing-impaired listeners may have greater difficulty perceiving masked speech, because they are more susceptible than normal-hearing individuals to the sound attenuation caused by the mask and depend more strongly on lip reading during conversation. Recent surveys have shown that hearing-impaired listeners were significantly more affected by masked speech than those without hearing impairment ( Saunders et al, 2021 ; Poon and Jenstad, 2022 ). Two behavioral studies reported that the adverse effect of masks on speech perception is greater in hearing-impaired individuals than in normal-hearing individuals ( Thibodeau et al, 2021 ; Alkharabsheh et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%